Food safety in the East African Community countries: Perceptions of key stakeholders in the food value chain - Kuboka, Maureen; Artursson, K.; Mutua, Florence K.; Lindahl, Johanna F.; Carlsson, G.; Grace, Delia (International Livestock Research Institute, 2022)
Introduction: Five of the six countries in the East Africa Community are classified by the WHO under the AFR-E sub-region. This sub-region is the second highest in foodborne disease burden with 1,200 DALYs per 100,000 inhabitants. Unsafe food has serious impacts on health and livelihoods of the people, as well as trade and economic development. Addressing food safety gaps requires participation of all stakeholders in the food value chain. Objectives: The objective of this study is to analyse the perceptions of relevant stakeholders on status of food safety, food safety gaps in informal markets and discuss opportunities to improve food safety in the region. Materials and methods: This is a qualitative study involving the use of participatory methods. Burundi and Kenya have purposely been selected for the study, with defined informal market settings. The protocols to guide data collection will be developed in English and translated to Swahili (for Kenya) and Kirundi (for Burundi), and pre-tested before use in the field. Ethical approvals in line with requirements in each country will be sought. Informed consent will also be obtained from all participants prior to their involvement in the study. Data will be summarized and synthesized thematically. Statistical methods for handling non-normal data will be considered. Results: The perceptions of stakeholders on status of food safety in informal markets and suggestions on priority value chains that should be considered for food safety intervention will be discussed. Conclusions: This study will provide in-depth understanding of food safety status in both countries, as perceived by the stakeholders. The findings are expected to guide future research work and further inform decision making for policy development and donor investment.